Editorial - Mattos, Amana; Souza, Alice De Marchi Pereira de; Ponciano, Edna Lúcia Tinoco; Degani-Carneiro, Filipe; Hernández, Jimena de Garay; Quadros, Laura Cristina de Toledo; Tura, Luiz Fernando; Brunhari, Marcos Vinicius; Quitério, Patrícia Lorena; Rapizo, Rosana Lazaro; Savegnago, Sabrina Dal Ongaro; Gomes, Vitor Castro (Estudos e Pesquisas em Psicologia, 2022)
Alice De Marchi Pereira de Souza, Edna Lúcia Tinoco Ponciano, Filipe Degani-Carneiro, Jimena de Garay Hernández, Laura Cristina de Toledo Quadros, Luiz Fernando Rangel Tura, Marcos Vinicius Brunhari, Patrícia Lorena Quitério, Rosana Lazaro Rapizo, Sabrina Dal Ongaro Savegnago, Vitor Castro Gomes